Career Trajectories of the Female Faculties in the Private Universities of Bangladesh: A Phenomenological Study - Tabassum, Tahsina; Rahman, Md. Sahidur (Society & Sustainability, 2020)
The education sector is considered as one of the suitable areas that facilitate women to pursue a prestigious career. Recently, along with public universities, private universities are significantly contributing to higher education in Bangladesh. Female faculties are building their careers in private universities. In university-level education, a faculty member plays a significant role in bringing out the talent hidden among the students and grooms them up for a future career. This study aims to trace the satisfaction, possible barrier, and progression prospect of the female faculties working in the private universities in Bangladesh. This study adopts a phenomenological research design to portrait the life experiences of ten female faculties regarding the respondents’ attraction to the teaching as a career, satisfaction issues (self-satisfaction, enjoyment, contentment, etc.), barriers (challenges in managing family, discontentment, stress, etc.), and dream about their career progression. This study tries to uphold an extensive understanding of female faculties’ thirst for involvement, struggle for difficulties, and motivation for advancement. The study sketches the career trajectories of female faculties in private universities, and it provides insight to the concerned authority to improve the working condition for the female faculties by taking proper steps.